On the relationship between ENSO and overland accumulated cyclone energy of landfalling tropical cyclones over the western North Pacific - Fu, Xinmiao; Song, Jinjie; Duan, Yihong (Frontiers in Earth Science, 2023)
This study investigates the relationship between El Niño-Southern Oscillation (ENSO) and overland accumulated cyclone energy (ACE) of tropical cyclones (TCs) over the western North Pacific (WNP). We find that there is only a weak correlation between ENSO and overland ACE during 1979-2019, compared to the significant relationship between ENSO and basinwide ACE over the WNP as reported in previous publications. Overland ACE is generally smaller in El Niño and La Niña years than that in neutral years, which mainly results from lower landfall frequency and shorter duration after landfall. Relative to neutral years, overland ACE is lower over almost the entire China mainland in both El Niño and La Niña years, which can be related to the change in the formation and movement of landfalling TCs. During El Niño and La Niña years, fewer landfalling TCs form over the western WNP, mainly resulting from reduced 850-hPa humidity, which leads to a less chance of TCs making landfall over China mainland. In addition, the eastward (westward) shift of the western Pacific subtropical high in El Niño (La Niña) years steers more TCs to make landfall over the southern (northern) China.